Postoperative analgesia in total knee arthroplasty - Mendoza-Aceves, Rodrigo A.; Gloria-Coronado, Paola G.; Madrid, Enrique Ortega; Yovanovich, Karen Meade; Zavala, Mónica Padilla; Banegas-Ruiz, Rodrigo; Gómez-Mendoza, Francisco Fabian; Soulé-Martínez, Christian E.; Barrera-Mera, Baltazar; Valderrama-Treviño, Alan I. (International Journal of Research in Medical Sciences, 2021)
Total knee arthroplasty is commonly performed in patients with end-stage osteoarthritis or rheumatic knee arthritis to relieve joint pain, increase mobility, and improve quality of life. Despite advances in surgical techniques, postoperative pain management in these types of patients is still deficient. An exhaustive review was performed with the available literature, using the PubMed, ScienceDirect, Scopus and Cochrane databases from 2004 to 2021. The search criteria were formulated to identify reports related to total knee replacement and pain management. Pain after total knee arthroplasty has been shown to involve both peripheral and central pain pathways, which is why various postoperative pain management strategies are currently applied, including patient-controlled analgesia, continuous peripheral nerve blocks, or single injection or local infiltration analgesia. Today local techniques such as periarticular injections are becoming more common in total knee replacement due to their effectiveness in controlling pain without causing muscle weakness. The development of minimally invasive techniques associated with multimodal and preventive analgesia improves recovery rates and early rehabilitation in patients undergoing total knee arthroplasty, reducing in-hospital costs, risk of complications, and improving patient satisfaction with chronic osteoarthropathy.